The Relationship between Social Support and Vaping Behavior of Senior High Age Adolescents in Surabaya - Blasius Hasni Damarjati; Sri Widati (Media Gizi Kesmas, 2022)
Background: Smoking has a negative impact on health in people of all ages, especially adolescents. With technological advancements, cigarettes have taken on a new form: e-cigarettes. The US Food and Drug Administration (FDA) has begun to prohibit the use of e-cigarettes because they contain hazardous and carcinogenic tobacco specific nitrosamines and diethylene glycol (DEG). However, e-cigarettes are becoming increasingly popular in Indonesia, with an increasing number of users.   Objectives: To investigate the relationship between social support on smoking/vaping behaviors of senior high age adolescents in Surabaya. Methods: This is a quantitative study with a cross-sectional and observational analytic design. The total number of respondents in this study was 145, as determined by the snowball sampling method. The independent variable is social support. Social support consists of instrumental support, informational support, emotional support, and appraisal support. The behavior of smoking/vaping is the dependent variable. Results: The relationship among variables was measured by using Pearson Chi-Square Test. The result shows that there is a relationship of instrumental support (p=0.000), informational support (0.019), emotional support (p=0.000), and appraisal support (p=0.000) on smoking / vaping behavior in senior high age adolescents. Conclusions: There is a relationship between social support and smoking / vaping behavior of high school age adolescents in Surabaya. Social support is important since it can influence the adolescents smoking behavior. It is hoped the family such as parents can provide a better understanding of the effect of smoking on health and for adolescents should be more selective with whom they hang out with and have the courage to refuse a friend's invitation to smoke.